The melodrama "Heroica in adversis constantia Thomae Mori" as an example of Olomouc Jesuit sodality theater production in the context of Holy Week - Förster, Josef (Moreana, 2024)
The story of Thomas More became the subject of dozens of plays on many European stages shortly after his death, including school plays, operas and oratorios, traveling theater troupe performances, burlesques, etc. With regard to Jesuit production in Europe, very few complete texts of plays have survived. In this respect, the Czech lands have a special position: Carolus Kolczawa's play Constantia in fide orthodoxa (1716) and the Jesuit melodrama Heroica in adversis constantia Thomae Mori (1727) have been preserved, the latter work in a set of 14 printed librettos of melodramas of the Olomouc Jesuit academic sodality. The Latin melodramas are related to the Lenten meditations and celebrations of this sodality during Passion Week and were performed on Palm Sundays. Our study will focus on a melodrama about Thomas More as a model of the theater production of the Olomouc Jesuit sodality during Passion Wee.